Asymmetrical Sexual Scripts in Y Literature: Manifestations of a Heteronormative Discourse - Phonkaewkate, Anantasak; Piayura, Orathai (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Issues surrounding gender and sexuality are fundamental determinants of either a liberated or restricted human experience, and comprehensive sex education has been recognized as an essential mechanism to help youth process their gender and sexuality in a standardized, open, safe, and healthy atmosphere. In the absence of such education, Y novels are a growing source of cultural resources in the social sphere of sexuality, especially among Thai girls and young women. The present study differentiated between and analyzed the sexual scripts engaged in by the two leading characters, the pra’ek and nai’ek, in scenes of erotic significance from nine such novels. The dialogue and narration from these scenes were analyzed descriptively, and clear patterns of asymmetry emerged. These patterns were discussed as manifestations of heteronormative discourses. Y novels, despite the same-sex relationships that define them, were found to re-produce heteronormative discourses around masculinity and femininity. While Y novels may be an avenue for girls and women to explore their own sexuality in the heteronormative context in which they find themselves, the genre may also endanger girls, women, and queer-identifying people by re-producing meaning making that defines a ‘gray area’ of consent in sexual encounters.